ปัจจัยเสี่ยงต่อการเสียชีวิตของทารกเกิดก่อนกำหนดในโรงพยาบาลมะการักษ์ - Kham-im, Boonluck (วารสารแพทย์เขต 4-5, 2018)
A retrospective study was performed to indentify risk factors of Premature Infant death in 1881 premature infants born between October 1, 1998 and September 30, 2001. Premature Infants occured in 2.94% of total birth and mortality rate was 2.82 per 1000 live birth. Data were analyzed by Chi - square test, Odds ratio and Logistic regression analysis. The results revealed that risk factors significantly associated with Premature infant death were birth weight less than 1,000 g (P < 0.01, OR = 53.45), gestational age less than 28 weeks (P < 0.01, OR = 42.000), Apgar score at 5 minute and 1 minute less than 7 (P < 0.01, 0.01 ; OR = 29.1, 8.96), on respirator (P < 0.01, OR = 42.37), Nosocomial infection (P <0.01, OR = 10.55) and inappropriated weight for age (P < 0.01, OR = 3.75). Logistic regression analysis identified only two variables, statistically significant effect on Premature infant death were birth weight less than 1,000g (P=0.015) and on respirator (P=0.015).